Kajian Aspek Reproduksi Ikan Endemik Bonti-bonti (Paratherina striata) di Danau Towuti, Sulawesi Selatau - Nasution, Syahroma Husni; Sulistiono, Sulistiono; Soedharman, Dedi; Muchsin, Ismudi; Wirjoatmodjo, Soetikno (Perhimpunan Biologi Indonesia, 2007)
ABSTRACTStudy of Reproduction Aspects of Endemic Fish Bonti-bonti (Paratherina striata)in Lake Towuti, South Sulawesi. Bonti-bonti, is one of endemic fishes in Lake Towuti andLake Mahalona. Bonti-bonti has been utilized by people around the lake for consumption inthe form of 6esh fish, dry fish, and salty fish; as ornamental fish; and as raw material foranimal feed. It should be protected from decreasing of fish population due to increasingexploitation and habitat quality changes. The objective of this research is to know thereproduction aspects of this endemic fish, as basic data for conservation. This research wasconducted in Lake Towuti, South Sulawesi from May 2006 to April 2007 at five stations.Samples were collected using experimental gillnet sized 0.625, 0.75, 1.0, and 1.25 inches.The result shows that testis and ovary was found each in one organ during a period of gonadadevelopment. Gonada maturity, was observed histologically oscured at five maturity stages.The range of egg diameters were from 0.01 to 1.50 mm. The fust gonada maturity period ofmale and female fish were reached at 5.53 and 6.26 cm of total length, respectively. Male andfemale fish gonada maturity (50%) were at 16.78 and 14.61 cm total length, respectively.Gonada maturity index value of male and female were 0.01-3.96% and 0.02-6.77%. Thereproduction ability is related to fecundity which have an effect on number ofjuveniles. Therange of fish fecundity were 818-6,051, which were devided kom female with 11.30-18.33cm total length. Bonti-bonti fish is partial spawner type.Key words : Reproduction aspects, endemic fish, Paratherina striata, and Lake Towuti